Policy Capacity of The Indonesian Government in Implementing Cross-Border Data Transfer Within Trade Agreements With The United States - Anitasari, Yuli; Sampurna , Agung Firman (Pelopor Publikasi Akademika, 2025)
The development of the global digital economy has encouraged the emergence of digital sovereignty issues, especially related to cross-border data transfer. In this context, the trade agreement between Indonesia and the United States announced in July 2025 includes Indonesia's commitment to open access to data transfer abroad. This commitment has strategic implications for national data governance and the protection of citizens' digital rights. This article aims to analyze Indonesia's readiness to implement these commitments using the policy capacity framework, which includes the government's technical, administrative, and political capacity. This study found significant limitations in all three dimensions of capacity, ranging from surveillance infrastructure to cross-agency coordination and political legitimacy. The analysis confirms the need for structured measures to strengthen institutions, procedures, and oversight so that the liberalization of data transfers does not come at the expense of digital sovereignty. This article contributes to the digital public policy literature by showing the application of the policy capacity framework in the issue of cross-border data transfer, which has been studied more from legal and economic perspectives.